2012
DOI: 10.1113/expphysiol.2011.063420
|View full text |Cite
|
Sign up to set email alerts
|

Explosive neuromuscular performance of males versus females

Abstract: The purpose of the study was to investigate sex-related differences in explosive muscular force production, as measured by electromechanical delay (EMD) and rate of force development (RFD), and to examine the physiological mechanisms responsible for any differences. The neuromuscular performance of untrained males (n = 20) and females (n = 20) was assessed during a series of isometric knee extension contractions; explosive and maximal voluntary efforts, as well as supramaximal evoked twitches and octets (eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
80
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 39 publications
12
80
1
Order By: Relevance
“…These findings may have been expected given the males' greater body mass and height, which have been shown to account for a significant portion of the variance in muscle size (Engel-Hoek et al 2012;Kawakami et al 1993). Moreover, our results are in agreement with those reported by previous authors, who demonstrated greater US CSA and/or MT values in males versus females for the biceps brachii (Arts et al 2010;Caresio et al 2014), vastus lateralis (Caresio et al 2014;Hannah et al 2012), rectus femoris (Caresio et al 2014), biceps femoris (Blackburn et al 2009), triceps brachii (Ichinose et al 1998;Kanehisa et al 1994), lateral gastrocnemius (Chow et al 2000), soleus (Chow et al 2000) and tibialis anterior (Arts et al 2010;Caresio et al 2014) muscles. For measurements of EI, however, previous US studies have revealed contrasting findings regarding differences between genders for the muscles of the upper and lower extremities (Arts et al 2010;Caresio et al 2014;Verhulst et al 2011).…”
Section: Discussionsupporting
confidence: 95%
“…These findings may have been expected given the males' greater body mass and height, which have been shown to account for a significant portion of the variance in muscle size (Engel-Hoek et al 2012;Kawakami et al 1993). Moreover, our results are in agreement with those reported by previous authors, who demonstrated greater US CSA and/or MT values in males versus females for the biceps brachii (Arts et al 2010;Caresio et al 2014), vastus lateralis (Caresio et al 2014;Hannah et al 2012), rectus femoris (Caresio et al 2014), biceps femoris (Blackburn et al 2009), triceps brachii (Ichinose et al 1998;Kanehisa et al 1994), lateral gastrocnemius (Chow et al 2000), soleus (Chow et al 2000) and tibialis anterior (Arts et al 2010;Caresio et al 2014) muscles. For measurements of EI, however, previous US studies have revealed contrasting findings regarding differences between genders for the muscles of the upper and lower extremities (Arts et al 2010;Caresio et al 2014;Verhulst et al 2011).…”
Section: Discussionsupporting
confidence: 95%
“…A potential key component that may contribute to the impaired power production following lengthening contractions is the rate of torque development (RTD) (Andersen and Aagaard 2006). The reduction in MVC following fatigue or lengthening contractions is associated with impaired RTD (Behrens et al 2012;Crameri et al 2007;Hannah et al 2012), and this would be manifested during dynamic contractions such that the ensuing angular velocity and power production will be reduced when the contractile torque equals and then exceeds the specific isotonic load.…”
Section: Introductionmentioning
confidence: 99%
“…Because torque production and RTD are impaired substantially following lengthening contractions (Behrens et al 2012;Crameri et al 2007;Hannah et al 2012), we hypothesized that there would be a greater loss of power at higher loads during dynamic shortening actions. However, due to less reliance on RTD to achieve the requisite isotonic load at a lower percentage of MVC, shortening velocity will be less impaired than at higher loads.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the work of Hannah et al (2012), it was hypothesized that maximum isometric strength would account for sex-differences in the maximum rate of torque development in the TA, because males and females are more comparable in maximum isometric strength in the lower limb. Studying mechanisms behind sex-differences in distal muscles that are responsible for balance and explosive activity can guide specific training interventions or rehabilitation techniques.…”
Section: Introductionmentioning
confidence: 99%